A MULTIPARTY COOPERATIVE MODEL FOR PESANTREN-BASED HALAL TOURISM DEVELOPMENT: STRENGTHENING THE LOCAL SHARIA ECONOMY IN BANYUMAS, INDONESIA - Sarpini; Siti Maghfiroh; Anis Supriyatin (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to analyze the role of a multiparty cooperative model in developing pesantren-based halal tourism and its contribution to strengthening the local sharia economic ecosystem in Banyumas Regency, Central Java, Indonesia. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, field observations, and document analysis involving pesantren leaders, cooperative managers, local communities, and tourism stakeholders. The data were analyzed using an interactive model, including data reduction, data display, and conclusion drawing, supported by triangulation techniques to ensure validity and reliability. The findings reveal that pesantren institutions play a strategic role as socio-religious and economic hubs in supporting halal tourism development. However, the absence of an integrated institutional framework limits the optimization of economic benefits. The study proposes a multiparty cooperative model that integrates pesantren, communities, government, and business actors. This model enhances coordination, promotes equitable resource distribution, and strengthens sectors such as halal culinary, religious tourism, and creative industries, contributing significantly to local economic resilience. This study is limited to a specific regional context, which may affect generalizability. However, it provides important implications for policymakers and practitioners in designing inclusive, community-based halal tourism strategies rooted in Islamic economic principles. This research offers a novel integrative model linking pesantren institutions, cooperative economics, and halal tourism within a unified framework. It contributes to the literature by demonstrating how Islamic social institutions can be operationalized to strengthen sustainable local sharia economies.